2021
DOI: 10.14245/ns.2040498.249
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Endplate Cyst Formation in Relation to Properties of Interbody Cages

Abstract: This retrospective study aimed to compare vertebral endplate cyst formation (VECF), an early predictor for pseudoarthrosis, in different types of interbody cages. Methods: We reviewed 84 cases treated with single-level posterior/transforaminal lumbar interbody fusion. We utilized a polyetheretherketone cage in 20 cases (group P), a titanium cage in 16 cases (group Ti), a titanium-coating polyetheretherketone cage in 13 cases (group TiP) and a porous tantalum cage in 35 cases (group Tn). VECF was evaluated comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recently, it has been reported that VECF after lumbar interbody fusion using a cage in the early postoperative period may be a predictor of pseudoarthrosis or non-fusion [ 39 ], and the relationship between VECF and non-fusion has been investigated for different types of interbody cages, including polyetheretherketone (PEEK), titanium, titanium-coated PEEK, and porous tantalum; however, no studies have investigated this relationship in patients treated using Ag-HA cages [ 39 , 40 ]. In the present study, cage subsidence occurred in three cases (5.9%) at 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that VECF after lumbar interbody fusion using a cage in the early postoperative period may be a predictor of pseudoarthrosis or non-fusion [ 39 ], and the relationship between VECF and non-fusion has been investigated for different types of interbody cages, including polyetheretherketone (PEEK), titanium, titanium-coated PEEK, and porous tantalum; however, no studies have investigated this relationship in patients treated using Ag-HA cages [ 39 , 40 ]. In the present study, cage subsidence occurred in three cases (5.9%) at 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the suitability of VECF as an indicator of bone fusion, at 12 months postoperatively, we noted VECF incidences of 13.7% to 60% in the PEEK cage group, 0–17.3% in the titanium cage group, and 21.6% in the Ag-HA cage group. Thus, the PEEK cage tends to be associated with a higher incidence of VECF [ 39 , 40 ], which seems true for the Ag-HA and titanium cages. The respective rates of VECF and bone fusion were 29% and 88% at 6 months after surgery and 22% and 91% at 12 months after surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%